Faulty bloodline eaudiobook - Gerlacher, Gary (AJ Docker Medical Thriller, 2024)
AJ Docker (Doc) and his guard dog, Banshee, move to a small town in the mountains for a slower-paced lifestyle. Doc settles into the idyllic setting with a rewarding job and enriching colleagues, as well as with a romantic interest who leads him to contemplate marriage. His new life seems perfect until he begins to uncover the town's dirty secrets. A serial killer hunts in the woods, and dirty money flows throughout the town. Doc and Banshee win allies in their search for truth, but they also make powerful enemies. These sophisticated figures who control the town's economy will stop at nothing to end Doc's threat to expose them. Doc must fight for his freedom, and even for his life to escape.